The Faint Sound of the Coast: A Study of the Adaptation of Aru Bay Fishers to Climate Change through the Sustainable Livelihood Framework Approach - Ita Musfirowati Hanika; Ilham Ayatullah Syamtar; Vivi Varlina; Resista Vikaliana; Muhammad Nur Ahadi; Farah Mulyasari (Dinasti International Journal of Education Management and Social Science, 2025)
Climate change has had a significant impact on the sustainability of coastal communities, particularly small-scale fishers who depend on the stability of marine ecosystems for their livelihoods. This study aims to understand the forms of adaptation undertaken by fishing communities in Aru Bay, South Kalimantan, and examine how these adaptations relate to existing institutional support and policy frameworks. Using a qualitative case study approach and analysis based on the Sustainable Livelihood Framework (SLF), this study explores ive forms of livelihood capital human, social, natural, physical, and financial that shape fishers’ adaptation strategies. Data were obtained through in-depth interviews with nine key informants, including active fishermen, fishermen's families, and the local village head. The results show that fishermen's adaptation process occurs autonomously and is heavily influenced by local experiences, social relations, and their interpretations of seasonal changes and extreme weather. Adaptation occurs through adjusting fishing times and locations, diversifying income, and establishing informal social networks. However, limited access to technology, financing, and social protection remains a significant barrier. These findings are expected to form the basis for developing more contextual and inclusive policies in response to the challenges of climate change in the small-scale fisheries sector